Paratuberculosis: new histopathological findings in red deer (Cervus elaphus) and fallow deer (Dama dama) in Chile - Lobão-Tello,Esteban Reyes (2017)
ABSTRACT: Paratuberculosis is a disease caused by Mycobacterium avium subsp. paratuberculosis (MAP) that affects domestic and wild ruminants. The most common gross lesions are emaciation and corrugation and thickening of the mucosa of the small intestine. Mesenteric lymph nodes might be enlarged. For the present study, 14 red deer and 9 fallow deer from game reserves or venison farms were analyzed. The lesions found correspond to those found by other authors in other geographic locations, except for some differences in histopathological examinations. Among these differences, stands out that intestinal lesions were concentrated mostly in the ileum and granulomas were shown to be more frequent in this section of the intestine than in the corresponding lymph node. Furthermore, in multibacillary lesions the inflammatory infiltrate in the lymph nodes was mainly composed of macrophages. These differences may be due to individual variations of the animals, the stage of disease or a different strain of the pathogen. This study allowed to obtain basic information about the disease and to describe patterns of lesions found in red deer and fallow deer with prediagnosis of clinical paratuberculosis which were not described in the literature before.